Contribution of Thrombospondin-1 and -2 to Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome - Qiang Li; Xiaoxiao Fu; Jiang Yuan; Shu Han (Mediators of Inflammation)
Thrombospondin (TSP) proteins have been shown to impact T-cell adhesion, migration, differentiation, and apoptosis. Thrombospondin-1 (TSP-1) is specifically upregulated in several inflammatory diseases and can effectively promote lipopolysaccharide- (LPS-) induced inflammation. In contrast, thrombospondin-2 (TSP-2) has been associated with activation of “anti-inflammatory” T-regulatory cells (Tregs). In this study, we investigated the effects of both TSP-1 and TSP-2 overexpression on macrophage polarization and activation in vitro and in vivo. We analyzed the effects of TSP-1 and TSP-2 on inflammation, vascular endothelial permeability, edema, ultrastructural morphology, and apoptosis in lung tissues of an ARDS mouse model and cultured macrophages. Our results demonstrated that TSP-2 overexpression effectively attenuated LPS-induced ARDS in vivo and promoted M2 macrophage phenotype polarization in vitro. Furthermore, TSP-2 played a role in regulating pulmonary vascular barrier leakage by activating the PI3K/Akt pathway. Overall, our findings indicate that TSP-2 can modulate inflammation and could therefore be a potential therapeutic target against LPS-induced ARDS.